Relationship Between Auditory Context and Visual Distance Perception: Effect of Musical Expertise in the Ability to Translate Reverberation Cues Into Room-Size Perception - Etchemendy, Pablo Esteban (2018)
In a recently published work by our group [Scientific Reports, 7, 7189 (2017)], we performed experiments of visual distance perception in two dark rooms with extremely different reverberation times: one anechoic (T ∼ 0.12 s) and the other reverberant (T ∼ 4 s). The perceived distance of the targets was systematically greater in the reverberant room when contrasted to the anechoic chamber. Participants also provided auditorily perceived room-size ratings which were greater for the reverberant room. Our hypothesis was that distance estimates are affected by room size, resulting in farther responses for the room perceived larger. Of much importance to the task was the subjects’ ability to infer room size from reverberation. In this article, we report a postanalysis showing that participants having musical expertise were better able to extract and translate reverberation cues into room-size information than nonmusicians. However, the degree to which musical expertise affects visual distance estimates remains unclear.